1993
DOI: 10.1021/ac00068a015
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific carbohydrate identification in recombinant proteins using MALD-TOF MS

Abstract: The utility of matrix-assisted laser desorption time-of-flight (MALD-TOF) mass spectrometry for the analysis of recombinant glycopeptides is discussed and compared to information which may be obtained by fast atom bombardment mass spectrometry (FABMS) and tandem mass spectrometry (MS/MS). MALD-TOF appears to be 10-100 times more sensitive than FAB MS for the analysis of underivatized glycopeptides, providing qualitative site-specific information regarding the carbohydrate microheterogeneity without the extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
95
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(98 citation statements)
references
References 8 publications
2
95
0
1
Order By: Relevance
“…Recently, high-energy CID fragmentation, including X-type cross-ring cleavage ions, has been observed for a variety of nonacidic oligosaccharides using matrix-assisted laser desorption/ionization (MALDI) tandem time-of-flight analyzers [4,5]. However, since fragile oligosaccharides, particularly polysialylated [6], and polysulfated molecules [7,8] have been observed to undergo prompt fragmentation in the vacuum MALDI source and metastable decomposition in the analyzer, they are more amenable to electrospray ionization. Negatively charged neutral oligosaccharides undergo fragmentation at very low collision energies [9 -11], and such ions are also more amenable to electrospray ionization than MALDI.…”
mentioning
confidence: 99%
“…Recently, high-energy CID fragmentation, including X-type cross-ring cleavage ions, has been observed for a variety of nonacidic oligosaccharides using matrix-assisted laser desorption/ionization (MALDI) tandem time-of-flight analyzers [4,5]. However, since fragile oligosaccharides, particularly polysialylated [6], and polysulfated molecules [7,8] have been observed to undergo prompt fragmentation in the vacuum MALDI source and metastable decomposition in the analyzer, they are more amenable to electrospray ionization. Negatively charged neutral oligosaccharides undergo fragmentation at very low collision energies [9 -11], and such ions are also more amenable to electrospray ionization than MALDI.…”
mentioning
confidence: 99%
“…M atrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) developed by Karas and Hillenkamp [1][2][3] has become a versatile and important tool for the determination of molecular masses of various fragile and nonvolatile samples such as proteins and carbohydrates [2,4,5]. Some success in the use of MALDI-TOF MS for the characterization of many low molecular weight compounds has been reported [6 -11].…”
mentioning
confidence: 99%
“…In addition, we have observed that in insect cells Am25 appears to be glycosylated cotranslationally, whereas Am97 may be glycosylated later on, probably after dimerization of the monomers has taken place Analysis of the glycans of IFN-y at different sites was performed by means of MALDI-MS combined with digestion with specific proteases and glycosidases. This is a newly developed technique for structural analysis of glycans and in the past few years has been used for site-specific analysis of protein glycosylation [27,[42][43][44]. The advantages of the technique are fast analysis, high sensitivity, and the ability to directly detect the many components caused by glycan heterogeneity.…”
mentioning
confidence: 99%